Maternal-Fetal Endocrine Interface: A Systematic Review of the Clinicopathological Assessment of Hypothalamic-Pituitary-Adrenal Axis Dysregulation in Pregnancy Complications - Fatima Bibi; Ome Kulsoom; Maria Khalid; Shama Chaudhry; Rehana Yasmeen; Shazia Sultana; Aneesa Khalid (Pakistan Journal of Medicine and Dentistry)
Background: The hypothalamic-pituitary-adrenal (HPA) axis played a critical role in balancing maternal stress responses during pregnancy. This systematic review aimed to evaluate the dysregulation of the HPA axis and its link to pregnancy complications.